Peningkatan Produktivitas BUMdes Barokah Desa Gredek Kabupaten Gresik - Surianto, Mohammad Agung; Umaimah, Umaimah (JURNAL PENGABDIAN MANAJEMEN, 2021)
This Service Program aims to develop the Barokah BUMDes business in Gredek Village, Gresik Regency based on local potential and strengthen governance so that BUMDes’ performance gets better and contributes to the income and welfare of all villagers. The basis for formulating the goals of the service program refers to the results of observations (surveys) and preliminary interviews with the director of BUMDes Barokah, Gredek Village, Sit Sampeyan District, Gresik Regency who expressed his desire to increase productivity while developing BUMDes business and financial administration management capabilities so that BUMDes can be accountable and not become a money laundry institution. The existing business units are still not based on processing the main village products, namely agricultural villages where the majority of the residents work as rice farmers. The solution in an effort to develop the business and governance of BUMDes Barokah is by: (1) creating potential transactions for basic village needs, which have been created independently so far, will be managed as the Gredek village market (2) creating the potential of the Gredek village reservoir, which so far has only functioned as a place for irrigation and fish farming, will be packaged into fishing tourism with fish cultivation targeted at bringing in tourists who have a hobby of fishing as well as educational tours for elementary school students or playgroups with the potential for beautiful panoramic views. village rice fields.